Economically Oriented Parenting Patterns in Families: Implications for the Learning Commitment of Grade XII Students at MA Bustanul Ulum Pati - Mahmud Alam Marzuqi (ANWARUL, 2026)
This study examines how economically oriented parenting patterns affect learning commitment among twelfth-grade students at MA Bustanul Ulum, Pati Regency. Drawing on constructivist epistemology, this qualitative study involved 30 students engaged in economic activities, their parents, and relevant teachers, selected through purposive and snowball sampling. Data were collected through semi-structured interviews, participant and non-participant observations, and document review, and were analyzed using Miles and Huberman’s interactive model. Triangulation, member checking, and audit trails were employed to ensure trustworthiness. The findings identify two predominant parenting patterns: supportive-productive parenting (60%) and pragmatic-economic parenting (40%). Students from supportive-productive families demonstrated stronger learning commitment, reflected in consistent study routines, active classroom participation, timely assignment completion, and future educational orientation. This pattern emerged because parents combined students’ economic involvement with emotional support, learning supervision, and flexible time management. In contrast, pragmatic-economic families prioritized immediate financial contributions, resulting in role conflict, irregular study schedules, reduced intrinsic motivation, and lower academic engagement. Although 21 of the 30 students participated in economic activities, the impact on learning commitment depended on how families integrated work responsibilities with educational expectations. The study concludes that economic constraints do not deterministically reduce students’ learning commitment; rather, parental framing, interaction quality, and educational expectations mediate students’ academic engagement. These findings contribute to the literature on family education and student commitment by highlighting the relational mechanisms through which economically oriented parenting shapes learning behavior. Practical implications include family-focused interventions, parenting training, flexible school schedules, scholarships, and temporary economic assistance to help students reconcile work and study responsibilities.